Mediating Effect of Management Accounting System on The Relationship Between Competition and Performance - Galih Fajar Muttaqin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Politeknik Piksi Input Serang, 2022)
Purpose - This study aims to investigate the role of management accounting systems in mediating the relationship between competition and managerial performance in manufacturing companies in Banten Design/method/approach - Respondents in this study were middle managers in manufacturing companies in Banten. The choice of respondents using purposive sampling technique and data collection of respondents using the survey method. Partial Least Square is a data analysis technique used in this study Finding - The results of the study show that there is a positive relationship between competition and the management accounting system on performance. In addition, competition can supply a positive and considerable influence. SA, accounting systems play a role in mediating competition and performance. Originality - This research was conducted to supply an overview of the role of the management accounting system in influencing the level of competition in manufacturing companies in Banten which has an impact on performance.